Litter environment affects behavior and brain metabolic activity of adult knockout mice - Crews, David; Rushworth, David; Gonzalez-Lima, Francisco; Ogawa, Sonoko (Frontiers in Behavioral Neuroscience, 2009)
In mammals, the formative environment for social and anxiety-related behaviors is the family unit; in the case of rodents, this is the litter and the mother-young bond. A deciding factor in this environment is the sex ratio of the litter and, in the case of mice lacking functional copies of gene(s), the ratio of the various genotypes in the litter. Both Sex and Genotype ratios of the litter affect the nature and quality of the individual’s behavior later in adulthood, as well as metabolic activity in brain nuclei that underlie these behaviors. Mice were raised in litters reconstituted shortly after to birth to control for Sex ratio and Genotype ratio (wild type pups vs. pups lacking a functional estrogen receptor α). In both males and females the Sex and Genotype of siblings in the litter affected aggressive behaviors as well as patterns of metabolic activity in limbic nuclei in the social behavior network later in adulthood. Further, this pattern in males varied depending upon the Genotype of their brothers and sisters. Principal Components Analysis revealed two components comprised of several amygdalar and hypothalamic nuclei; the VMH showed strong correlations in both clusters, suggesting its pivotal nature in the organization of two neural networks.